Long-term outcomes and aggressiveness of hereditary medullary thyroid carcinoma: 40 years of experience at one center - Raue, Friedhelm; Bruckner, Thomas; Frank-Raue, Karin (The journal of clinical endocrinology & metabolism, 2019)
The present observational study of 263 patients with MEN2 revealed no differences in clinical outcomes between the MOD and H groups. However, the outcomes in th